1978
DOI: 10.3146/i0095-3679-5-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Biochemical Parameters of Callus Growth from Three Peanut Cultivars1

Abstract: The phytohormones 2,4-dichlorophenoxyacetic acid, naphthalene acetic acid and kinetin nave been employed to induce callus growth from the cotyledon tissue of three commercial peanut cultivars: ‘Early Bunch’ (EB), ‘NC-Fla 14’ (NC) and ‘Florunner’ (FR). Cultivar specific parameters have been examined for both cotyledon and callus tissue. The relative growth rates of callus tissues were always EB>NC>FR. SDS-polyacrylamide gel electrophoresis performed on the proteins from both types of tissue demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Callus is generally easy to produce in Arachis but plant regeneration is difficult. Peanut cotyledons have been used to define biochemical parameters for callus growth in cultivars (Verma and van Huystee, 1971;Verma and Marcus, 1974;Russo and Varnell, 1978;Guy et al, 1978). However, regeneration of plants from cotyledon callus of peanuts has not been obtained.…”
Section: Cell and Protoplast Culturementioning
confidence: 99%
“…Callus is generally easy to produce in Arachis but plant regeneration is difficult. Peanut cotyledons have been used to define biochemical parameters for callus growth in cultivars (Verma and van Huystee, 1971;Verma and Marcus, 1974;Russo and Varnell, 1978;Guy et al, 1978). However, regeneration of plants from cotyledon callus of peanuts has not been obtained.…”
Section: Cell and Protoplast Culturementioning
confidence: 99%
“…The growth factors needed for the generation of callus from peanut plant tissue have been described by Joshi and Noggle (14), Joshi and Ball (13), Kumar (16), and Guy et al (10). Martin (19) and Martin and Rabechault (20) describe growth factors for culturing peanut ovules or anthers in which limited success was obtained.…”
mentioning
confidence: 97%
“…Organogenesis and multiple bud formation (Illingsworth 1968, Guy et al 1978, Sastfi et al 1982, Narasimhulu and Reddy 1983, Bhatia et al 1985, Mhatre et al 1985, Seitz et al 1987, McKently et al 1990, 1991 and recently somatic embryogenesis have been reported in drachis (Hazra et al 1989, Ozias-Akins 1989. The aim of presented communication, was the induction of somatic embryos from immature cotyledons and embryonal axis of ,4. hypogaea and the establishment of the embryo-derived plants in the field.…”
Section: Introductionmentioning
confidence: 92%